207 Maternal Fatty Acids Intake During Pregnancy and Later Child Cognitive Development in the Eden Mother-Child Cohort Study. (October 2012) - Bernard, JY; Agostini, M de; Forhan, A; Champion, V; Kaminski, M; Charles, MA; Heude, B
Abstract : Background and aims: Polyunsaturated Fatty Acids (PUFA) are needed for child brain development, especially n -3 PUFAs. Prenatal exposure depends on maternal lipids intake during pregnancy. We aimed to investigate associations between maternal PUFAs intake during pregnancy and later child cognitive development. Methods: In 1066 children of the EDEN mother-child cohort, we assessed cognitive development at 3 years with the Ages and Stages Questionnaire (ASQ, score between 0 and 300). Maternal lipids intake during pregnancy was evaluated after delivery, using a food frequency questionnaire and a food-composition table. We investigated associations between PUFAs intake and ASQ score using multiple linear regressions adjusted for centre, child's age, gender and gestational age, maternal tobacco and alcohol consumptions, parental education, siblings, caregivers and preschool attendance. Results: Mean ASQ score was 270.1 (±29.4), n -6/ n -3 ratio in food intake was 10.0 (±2.3) and total n -3 PUFAs intake was 0.47% (±0.09) of total energy intake. In crude analyzes, ASQ score was positively associated with each three n -3 PUFAs (α-linolenic, eicosapentaenoic and docosapentaenoic acids) and negatively with linoleic acid and n -6/ n -3 ratio. After adjustment, ASQ score remained significantly associated with n -6/ n -3 ratio (β= –1.16; SE=0.37; P =0.0015). Association with total n -3 PUFAs tended to persist (β=1834; SE=985; P =0.063). Conclusions: After adjustment for confounders, especially maternal education, higher n -3 PUFAs intake and thus lower n -6/ n -3 ratio in pregnancy food consumption were associated with better cognitive development in early childhood. We observed similar results with prepregnancy lipids intake. Our study suggests a role of prenatal nutrition on childhood cognitive development.